Peran Media Sosial dalam Menciptakan Personal Branding Seseorang - Fawwazzain Sukmawan (Comit: Communication, Information and Technology Journal, 2025)
In the digital era where everything can be connected, social media has become the main platform for individuals to build and manage their personal image. This research explores the role of social media in creating personal identity, with a focus on strategy, influence and impact on individual reputation. This journal identifies the main factors that contribute to the success of personal branding through social media, including management of relevant and interesting content, active interaction with followers, and consistency in the messages conveyed. Through a comprehensive literature analysis, this research also explores how intense exposure to social media can influence public perceptions of individuals, both positively and negatively. Additionally, the research also considers the psychological impact of constantly digital living, such as increased self-confidence or stress associated with high expectations. This review provides valuable insight into best practices in building effective personal branding in the digital age, while recognizing the challenges and risks associated with reliance on social media as a primary tool for influencing self-image. These findings are relevant for individuals looking to optimize their online presence, as well as for marketing professionals and researchers interested in the complex dynamics behind the use of social media as a strategic tool in building and maintaining personal branding.